The Effect of Financial Risk on Financial Performance in the Non-Cyclical Consumer Industry Listed on the BEI - Dwi Wijayanty; Monic Indrianisca; Astrid Dila Aurelia; Laras Olivia; Farah Margaretha Leon (UNIVED Press, 2024)
Financial performance refers to the assessment of a company's accomplishments concerning its overall health within a specific timeframe. This study aimed to investigate the impact of financial risk on the financial performance of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange. The objective was to analyze how financial risk influences operational risk, market risk, liquidity risk, credit risk, solvency risk, and control variables, namely company size and leverage, on return on equity-a key metric for measuring financial performance. The study focused on the 52 non-cyclical consumer industry companies listed on the Indonesian Stock Exchange for the period spanning from 2018 to 2022. Employing a quantitative approach, the research utilized secondary data collected from audited annual reports. Panel data regression models were employed for testing purposes. The findings revealed that market risk and credit risk exerted a negative influence on financial performance, whereas liquidity risk, solvency risk, and operational risk demonstrated no significant impact on financial performance. The implications of this research provide financial managers with insights into optimizing financial performance to attain organizational objectives, particularly in enhancing shareholder welfare.